2012
DOI: 10.2174/187152412802430156
|View full text |Cite
|
Sign up to set email alerts
|

The Atypical Cannabinoid O-1602: Targets, Actions, and the Central Nervous System

Abstract: O-1602 is a cannabidiol analogue that does not bind with high affinity to either the cannabinoid CB1 receptor or CB2 receptor. However, there is evidence that O-1602 has significant effects in the central nervous system as well as other parts of the body. Depending upon the model, O-1602 has anti-inflammatory or pronociceptive effects, mediated through a number of distinct receptors. This article reviews the evidence for functional effects of O-1602, particularly in the CNS, and describes its known targets as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 44 publications
1
24
0
1
Order By: Relevance
“…Some recent studies have suggested targets other than GPR55 receptors for O-1602. For example, it was reported that O-1602 also has affinity for GPR18 receptors [25]. The results also showed that ML193 induced anxiogenic-like effects with a decrease in spontaneous locomotor activity at the highest dose.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Some recent studies have suggested targets other than GPR55 receptors for O-1602. For example, it was reported that O-1602 also has affinity for GPR18 receptors [25]. The results also showed that ML193 induced anxiogenic-like effects with a decrease in spontaneous locomotor activity at the highest dose.…”
Section: Discussionmentioning
confidence: 79%
“…Some recent studies have suggested targets other than GPR55 receptors for O‐1602. For example, it was reported that O‐1602 also has affinity for GPR18 receptors . For evaluation of the role of GPR55 receptors in O‐1602‐induced anxiolysis, both ML193 (as an antagonist of GPR55 receptor) and O‐1602 were injected with a 5 min interval.…”
Section: Discussionmentioning
confidence: 99%
“…O-1602 has also been shown to increase levels of GPR18-mediated MAPK activity and calcium mobilization, but not β-arrestin signaling, thus supporting that O-1602 acts as a biased-agonist at GPR18 (Console-Bram et al, 2014). Data have been reported suggesting the therapeutic potential of O-1602 for diseases related to the central nervous system (Ashton, 2012), or to metabolic diseases (Romero-Zerbo et al, 2011). …”
Section: Synthetic Cbd Analogsmentioning
confidence: 99%
“…However, the authors stated that “in the absence of an actual receptor response, expression of functional GPR18 receptors in this study remains to be determined” , hence, care must be taken when interpreting this study. Furthermore, the pharmacology of GPR18 and GPR55 is similar in that the synthetic ligands O‐1602 (agonist) and O‐1918 (antagonist) and Abn‐CBD (agonist) act on both these receptors . Therefore, it should be acknowledged that there are difficulties in interpreting studies utilizing these compounds in determining specific functions of either GPR18 or GPR55 when both receptors are expressed in the same tissue/cell and in vivo.…”
Section: Gpr18 Pharmacologymentioning
confidence: 99%